Concurrent DNA Copy‐Number Alterations and Mutations in Genes Related to Maintenance of Genome Stability in Uninvolved Mammary Glandular Tissue from Breast Cancer Patients. Issue 11 (14th August 2015) - Ronowicz, Anna; Janaszak‐Jasiecka, Anna; Skokowski, Jarosław; Madanecki, Piotr; Bartoszewski, Rafal; Bałut, Magdalena; Seroczyńska, Barbara; Kochan, Kinga; Bogdan, Adam; Butkus, Małgorzata; Pęksa, Rafał; Ratajska, Magdalena; et al.
<x xml:space="preserve">Abstract</x> Panel A of the Figure 1 may be used for the graphical Table of Contents. The relevant high resolution TIF file is attached to the author proof. Here is the text of the proposed description: "Somatic mosaicism for DNA copy‐number alterations (SMC‐CNAs) is defined as gain or loss of chromosomal segments in somatic cells within a single organism. Here, gross SMC‐CNAs (>500 kbp) were characterized in uninvolved mammary glandular tissue samples (6/59) from breast cancer patients, distal from the primary tumor site. These SMC‐CNAs co‐occurred with mutations and rare variants in genes related to maintenance of genomic integrity. Our results highlight the temporal and spatial neoplastic potential of uninvolved glandular tissue in breast cancer patients."